Insights into infant behavior and development from Latin America - Hermida, María Julia; Narea, Marigen; Singh, Leher; Cristia, Alejandrina (Elsevier, 2024)
This special issue focuses on a geographic region rather than a typical topic or theme. The reason is that Latin American research on infancy has been so underrepresented in mainstream journals that we felt it deserved a dedicated special issue. Focusing on a specific topic would have decreased the plurality of research as countries do not necessarily have research output in all areas, either due to a lack of resources or because those topics are relevant to the country. Additionally, Latin America has various common issues that define it as a region: a shared history of colonization, a higher number of Aboriginal inhabitants compared to other regions, and significant socioeconomic inequality both across the region and within each country. In sum, with this special issue, we aimed to highlight the research being conducted in the region.
Keywords: Ciencias sociales::Psicología